2013
DOI: 10.5430/elr.v2n2p31
|View full text |Cite
|
Sign up to set email alerts
|

Code Switching as an Interactive Tool in ESL Classrooms

Abstract: This study addresses the role of code switching to students' L1 (Arabic) in their ESL classrooms and whether it expands interaction in these classrooms. The gap perceived in this area needs to be addressed towards the domains of sociolinguistics and applied linguistics in the ESL classrooms teaching environment. Henceforth, this study draws on data collected from basic, secondary and college ESL classrooms in the Sudan and Saudi Arabia. The study incorporates various data gathering procedures: audio-taped spok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…This was meant not to confuse with many new words at one go but a few words bit by bit until I became a good speaker of Xitsonga. L2 [39] assert that code-switching can take place in a conversation when one speaker uses one language and the other speaker answers in a different language. According to [40], teachers switch the codes as a strategy to compensate for the deficiency on the part of students.…”
Section: Code-switchingmentioning
confidence: 99%
“…This was meant not to confuse with many new words at one go but a few words bit by bit until I became a good speaker of Xitsonga. L2 [39] assert that code-switching can take place in a conversation when one speaker uses one language and the other speaker answers in a different language. According to [40], teachers switch the codes as a strategy to compensate for the deficiency on the part of students.…”
Section: Code-switchingmentioning
confidence: 99%
“…However, some advanced learners prefer to use Arabic linguistic forms, even though they are capable to use the English equivalents as they believe that L2 forms miss the religious and cultural values of the original L1 concepts. Finally, Magid and Mugaddam (2013) addressed the role of students' CS to L1 (Arabic) in ESL classes in Sudan and Saudi Arabia. The results revealed that L1 (Arabic) had been helpful in expanding classroom interaction.…”
Section: Reasons For Cs In the Classroommentioning
confidence: 99%